Is Syndesmotic Screw Removal Needed Before Weight-Bearing Ambulation? - Jong-Kil Kim MD; Seong-Yup Jeong MD; Kwang-Bok Lee MD, PhD (Foot & Ankle Orthopaedics, 2016)
Category: Trauma Introduction/Purpose: In syndesmosis injury, numerous clinical and biomechanical investigations showed some concensus as follows; 1)There are no difference in stainless steel versus titanium screws. 2)A 4.5-mm screw apparently provides greater resistance to shear stress than a 3.5-mm screw. 3)The level of placement probably does not affect outcome. 4)Three-cortical versus four-cortical screw placement does not affect biomechanical stability. But, whether the syndesmosis screw should be removed prior to weight-bearing or not is still debated. The aim of this study is to compare the functional outcome between screw removal and retain group, and between diastasis and no diastasis group. Methods: One hundred twelve patients had undertaken open reduction and internal fixation due to syndesmosis injury, who divided into 4 groups; (A) syndesmotic screw removal before weight-bearing (postoperative 3 months, n=56) and (B) retained group (n=56), (C) recurrence of diastasis (n=16) and (D) no diastasis (n=40) after screw removal. Radiological diastasis, VAS, AOFAS ankle-hindfoot score, SF-12, complications (screw loosening and breakage) were evaluated between groups. Results: AOFAS ankle-hindfoot score shows 75.10±10.40 in group A, 77.07±10.60 in group B, and SF12 shows 45.78±5.68 in group A, 47.33±5.83 in group B, there is no significant difference between group A and B in AOFAS ankle-hindfoot score and SF- 12 (p=0.487, p=0.319). Radiological diastasis significantly develops (p=0.025) in group A (16/56) compare to B (2/56), but screw loosening or breakage significantly develops (p=0.001) in group B (8/56) compare to group A (0/56). AOFAS ankle-hindfoot score shows 70.33±6.22 in group C, 76.50±10.26 in group D, and SF12 shows 49.85±3.83 in group C, 47.40±8.01 in group D, there is no significant difference between group C and D in AOFAS ankle-hindfoot score and SF-12 (p=0.808, p=0.065). There is no significant difference between group C and D B in VAS, AOFAS ankle-hindfoot score and SF-12. Conclusion: Diastasis recurrence is significantly higher in removal group. But, screw retain group shows higher breakage, loosening rate than removal group. Clinical outcome such as VAS, AOFAS ankle-hindfoot score and SF-12 is no significant different in two groups.Also, if diastasis recurred, it did not affect clinical outcome. Therefore, we couldn’t conclude that syndesmotic screw removal is needed before weight-bearing (postoperaive 3 months).